Professional, educational, and psychological characteristics of kindergarten teachers in Ubari Municipality - Al-Tayeb, Abdul Jalil Al-Mahdi Al-Tayeb Mohammed (Sharwes Scientific Journal, 2025)
The researcher conducted a study titled "Professional, Educational, and Psychological Characteristics of Kindergarten Teachers." The study aimed to identify the professional, educational, and psychological characteristics of kindergarten teachers and nannies, explore the methods they employ, and uncover the key traits they believe they need to improve their job performance. Additionally, the study sought to identify the methods that contribute to the development of these characteristics. The study was limited to the professional, educational, and psychological characteristics of kindergarten teachers in the Ubari region. It was completed in the spring of 2023, and the researcher used a descriptive-analytical approach to examine the subject. The study population consisted of 100 kindergarten teachers and nannies in Ubari, with a random sample of 31 participants selected. The research instrument used was a "Professional, Educational, and Psychological Characteristics Scale" for kindergarten teachers and nannies, designed by the researcher to collect data. The tool was reviewed and validated for reliability and consistency using statistical methods, comprising 20 items. The key findings of this study: There were statistically significant differences in the availability of certain professional, educational, and psychological characteristics among kindergarten teachers in Ubari.  Also, there were statistically significant differences in the availability of these characteristics based on the variables of specialization and experience.